Rachel's holiday - Keyes, Marian (Perennial, 2002)
A high-flying young Irishwoman with a penchant for recreational drugs and men in tight leather crash lands in the Cloisters, Dublin's version of the Betty Ford Clinic, where group therapy and middle-aged men in sweaters will drive her nearly out of her mind.